Analysis of User Satisfaction Levels in the Shopee PayLater System using the User Experience Questionnaire (UEQ) - Aliyah Khofifah; Apriansyah Putra; Ari Wedhasmara; Mira Afrina (Universitas Islam Indragiri, 2026)
The rapid advancement of information technology in the digital era has triggered significant changes across various aspects of life, including the e-commerce sector. This study aims to analyze the level of user satisfaction with the Shopee PayLater system using the User Experience Questionnaire (UEQ) method. The research was motivated by the increasing use of PayLater services in e-commerce and the importance of evaluating user experience to improve system quality. This study employed a quantitative method using the User Experience Questionnaire (UEQ) approach, which consists of six dimensions: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Data were collected through questionnaires distributed to 100 students from the Faculty of Computer Science at Sriwijaya University and analyzed using the UEQ Data Analysis Tools. The results indicate that Shopee PayLater achieved positive user satisfaction across all UEQ dimensions. The highest scores were obtained in perspicuity (2.03), efficiency (1.89), dependability (1.89), and attractiveness (1.66), indicating that Shopee PayLater is easy to understand, efficient to use, and capable of providing user comfort. Meanwhile, the stimulation (1.65) and novelty (1.56) dimensions still require improvement through feature development and service innovation to create a more engaging user experience. In addition, the benchmark results show that all dimensions fall within the excellent category and are included in the top 10% of benchmark results, indicating a very high-quality user experience. Based on these findings, it can be concluded that Shopee PayLater provides an excellent user experience overall. However, the stimulation and novelty aspects still need enhancement through feature innovation and interface improvements to make the service more attractive and less monotonous for users.